A ‘Social Identity Approach’ as a Theory for the Design of Learning with Educational Technology: The Case of Clickers - Bowskill, Nicholas; Lally, Vic (Proceedings of the International Conference on Networked Learning, 2018)
This article explores learning design initially focussing upon clickers, a polling technology used largely in the classroom. We develop that to consider learning design focused at the level of the whole-group. We then apply this to education technologies in general. One distinctive contribution made here is to conceptualise clickers as a technology for groups to work as a group (collectively). To explore this, we consider two popular models for using clickers. One of these is Peer Instruction (Mazur) which is by far the most used and well-known model. The other is SharedThinking (Bowskill) which is a more recent addition. We go on from there to explore group-relevant theory and seek to widen this to consider theory for learning design using many technologies. Clickers are an under-theorised set of technologies and here is our second distinctive contribution in this paper. Researchers have called for ‘empirical work to develop theory’ (Boscardin and Penuel, 2012) for this technology. An additional concern is that ‘existing research does not connect to larger research on education or psychology’ (Penuel, Roschelle et al, 2004). We explore the possibility of a social identity approach (Bliuc et al., 2011, Haslam, 2004) as a theoretical tool for learning design in way which might address these concerns. We suggest learning design may benefit from a focus on the group-level of thinking as part of a technology-supported identity-mediated practice. Interestingly, other researchers have argued for different mediators of learning to be considered when designing pedagogical practice. Technology and networks (Siemens, 2005), language (Wertsch, 1980, Vygotsky, 1978), activities and tools (Engeström, 2007) and communities (Wenger, 1998, Lave and Wenger, 1991, Roschelle et al., 2004) have all been used to inform pedagogy. This paper proposes the addition of ‘identity-mediated group learning’ (Bowskill, 2017b) in which the situated group-identity provides the basis for development using a social identity approach. Finally, one researcher describes the use of clickers as having a ‘catalytic’ effect (Draper, 2009). Another notes the ’sense of community’ as an affective outcome arising from the use of this technology (Simon et al., 2013). In this paper, the suggestion is the ‘catalytic’ effect may be the moment of social identification when the group is made salient and deindividuation occurs. From this, we affirm the view elsewhere in the literature that ‘reference to peers has more influence than reference to facts’ (Goldstein et al., 2008).